Vidéo de présentation du projet USAID/CINSERE - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Crops Research Institute for the Semi-Arid Tropics; United States Agency for International Development; Agence Nationale de l'Aviation Civile et de la Météorologie (2021)
Vidéo de présentation du projet USAID/CINSERE